2010
DOI: 10.1016/j.ijid.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Structured interruptions of highly active antiretroviral therapy in cycles of 4 weeks off/12 weeks on therapy in children having a chronically undetectable viral load cause progressively smaller viral rebounds

Abstract: The STI of HAART in cycles of 4 weeks off/12 weeks on therapy in children with chronically undetectable VL can cause progressively lower viral rebounds followed by a decrease to undetectable levels, with a low risk of severe immunosuppression and without the occurrence of symptoms related to HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 32 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…One reason for our observed shorter TI is that our CD4% criterion for ART restart was higher (25%) to align with later WHO recommendations[22], while PENTA-11 and CHER used CD4% of 20% eligibility for ART restart. Small pediatric TI studies have observed CD4% increase following initial decline as HIV-1 specific immunity increases in response to viremia emerging after TI [23]. Lower CD4% criteria for ART re-start may permit time to develop HIV-specific immunity to contain virus and regain immune reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for our observed shorter TI is that our CD4% criterion for ART restart was higher (25%) to align with later WHO recommendations[22], while PENTA-11 and CHER used CD4% of 20% eligibility for ART restart. Small pediatric TI studies have observed CD4% increase following initial decline as HIV-1 specific immunity increases in response to viremia emerging after TI [23]. Lower CD4% criteria for ART re-start may permit time to develop HIV-specific immunity to contain virus and regain immune reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, evaluation of Structured Treatment Interruptions (STI) has been proposed as an alternative therapeutic strategy to reduce complications associated with continuous HAART administration [ 1 ]. Based on the establishment of treatment periods followed by drug-free periods long enough to allow significant viral rebound but with a controlled maintenance of the viral replication [ 2 ], STI could induce an increase of the HIV-specific immune response and, consequently, progressively smaller viral rebounds [ 3 , 4 ]. However, information available about STI in pediatric patients remains limited and such information in adults is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…These treatment strategies have received increasing attention in recent years, but their efficacy and safety have been controversial. Many studies have considered specific STI strategies involving different interruption intervals and decision rules for stopping and initiating therapy [17,20,23,28]. Tang et al [28] use a piecewise model of HIV dynamics to explore STI strategies guided by CD4+ T cell counts.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al [28] use a piecewise model of HIV dynamics to explore STI strategies guided by CD4+ T cell counts. Palacios et al [20] examine the viral, immune, and clinical impacts of a STI program in three cycles of 12 weeks on and 4 weeks off on children infected with HIV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation